Assessment of the Impacts of Climate Change on the Water Allocation, Water Quality and Salmon Production in the San Joaquin River Basin - Hidalgo León, Hugo G. (2006)
2 Assessment of the Impacts of Climate Change on the Water Allocation, Water Quality and Salmon Production in the San Joaquin River Basin H. Hidalgo, L. Brekke, N. Miller, N. Quinn, J. Keyantash and J. Dracup INTRODUCTION California’s climate and geography make its agro-economic and environmental welfare particularly vulnerable to the impacts of climate change. The majority of California’s water supply (without the Colorado River imports) arrives during the winter months in the high elevations. This water is stored as snowpack and is available only during the spring snowmelt. Conversely, a large part of the water demand for agricultural uses occurs during the summer months, particularly in the Central Valley. This disjoint timing of water supply relative to demand imposes challenges in the management of California’s water resources (Hidalgo et al. 2005). Climate change could potentially alter different aspects of the water supply in the headwaters and of the demand in the Central Valley. These changes will ultimately translate into impacts in the environment and agricultural production, an essential source of income and employment for the state. California is the highest ranked state in terms of added-value of agricultural production and the sixth largest agricultural exporter in the world (DWR 1998). The different agricultural activities in the Central Valley represent approximately 6–7 percent of the total income, employment and added-value of the state’s trillion-dollar economy. In the San Joaquin Valley, the most agriculturally intensive region in the Central Valley, agriculture represents 32 percent of the total income, 28 percent...